The Effect of Propofol on Chronic Headaches in Patients Undergoing Endoscopy - David Giampetro; Victor Ruiz-Velasco; Ashlee Pruett; Matthew Wicklund; Robert Knipe (Pain Research and Management)
Objective. This study determined acute and long-term effects of propofol administration in patients with severe headaches undergoing endoscopic procedures. Background. Approximately 13% of the US population is affected by migraines or severe headaches. The effect of propofol on headaches more than a few days after the intervention has not been explored. Methods. We employed a nonrandomized, prospective observational study that recruited patients with chronic headaches who received propofol from an outpatient endoscopy center for either upper or lower endoscopies. Patients completed the six-item Headache Impact Test (HIT-6) questionnaire prior to the procedure and 30 days after endoscopy. Additionally, the patients’ response to propofol two days after endoscopy was assessed via phone. Results. The age of the participants (n=31) ranged from 20 to 70 years. The mean HIT-6 composite scores were significantly lower (p<0.05) 30 days after propofol administration when compared to baseline scores. Upon stratification, 23 patients indicated an improved condition, 7 a worsened outcome, and 1 showed no change. Furthermore, mean scores were significantly lower (p<0.05) in three HIT-6 questions pertaining to the severity of pain, daily activity, and frequency of lying down. Finally, the mean pain score obtained was significantly lower (p<0.05) two days after procedure. Conclusions. The results of this suggest that propofol administration should be considered in treating chronic headaches. Double-blind studies are necessary to confirm these results.